Road Intersection As Stormwater Detention Basin - Mah, D.Y.S.; Siew, Ling Loh; Gabriella Sabatini, Anak Poul; Wan Hashim, Wan Ibrahim (IAHR World Congress, 2017)
This study is exploring the potential of transforming road junction with dual functions in supporting traffic flow and accommodating stormwater detention. High loading capacity in specialist concrete could be used to construct precast concrete modular units, as it could be strong enough to allow passing of vehicles. It could also be molded to form hallow chambers that function as temporary stormwater storage. A modelling case study is presented to showcase the application of such stormwater on-site detention system. Initial modelling has indicated that the design could reduce the flow of urban runoff by 40-50% on road surface; and the running water could be fully captured within a height 0.4 m of underground storage.